Using Kahoot! Improving seventh-graders' reading comprehension skills of SMPN 2 Tegalrejo - Dian Setyo Nugroho (Universitas Sarjanawiyata Tamansiswa, 2021)
This research was conducted to describe how the implementation of Kahoot! in the reading comprehension of seventh graders in SMPN 2 Tegalrejo. This research aims to: (1) to describe how the implementation of Kahoot! in the reading comprehension of seventh graders in SMPN 2 Tegalrejo, (2) describe the result of the use of Kahoot! to improve the reading comprehension of seventh graders in SMPN 2 Tegalrejo. The research was conducted by applying clasroom action research. There are four steps in conducting this research, namely: planning, action, observing, and reflection. It implemented two cycles which are cycle 1 and cycle 2. The data were collected by observation, interview, document analysis, and tests. Process of data analysis involved four activities; those are data collection, data reduction, data display, and conclusion drawing. Descriptive qualitative analysis was used to present the result of the study in the form of descriptive explanation. Kahoot! implemented to improve the students’ reading comprehension skill. The findings indicate that students were better at developing in identifying main idea and implicit information. Most of them could determine specific information. They also could determine the reference. Besides there is improvement in undersatnding vocabulary context. The average of students’ scores also improved as indicated by their average writing score of the Preliminary Test, Cycle 1, and Cycle 2 tests that were 58.04, 66.52, and 78.69, respectively. The last average score was higher than the minimum achievement criteria of 75.00.